2016
DOI: 10.1002/acr.23015
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Patients With Primary Sjögren's Syndrome and Systemic Lupus Erythematosus: A Comparative Registries‐Based Study

Abstract: Objective. To compare the prevalence of the main comorbidities in 2 large cohorts of patients with primary Sj€ ogren's syndrome (SS) and systemic lupus erythematosus (SLE), with a focus on cardiovascular (CV) diseases. Methods. This was a cross-sectional multicenter study where the prevalence of more relevant comorbidities in 2 cohorts was compared. Patients under followup from SJOGRENSER (Spanish Rheumatology Society Registry of Primary SS) and RELESSER (Spanish Rheumatology Society Registry of SLE), and who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…It is well-established that comorbidities significantly contribute to the morbidity and mortality of rheumatic diseases; however, available data on their relative frequency and impact are limited [ 10 – 13 ]. Herein, we compared the prevalence of the most frequent comorbidities in two well-matched cohorts of patients with SSc and RA; to our knowledge this is the first such comparative study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that comorbidities significantly contribute to the morbidity and mortality of rheumatic diseases; however, available data on their relative frequency and impact are limited [ 10 – 13 ]. Herein, we compared the prevalence of the most frequent comorbidities in two well-matched cohorts of patients with SSc and RA; to our knowledge this is the first such comparative study.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional cardiovascular risk factors, eg, arterial hypertension (OR 0.51; 95% CI 0.39–0.66), dyslipidemia (OR 0.77; 95% CI 0.61–0.98), and smoking (OR 0.39; 95% CI 0.29–0.51), were less frequent in the pSS group than in SLE patients without sSS 47. A similar finding was observed for stroke/myocardial infarction (OR 0.61; 95% CI 0.38–0.93) 47. The adjusted analysis for demographical characteristics, and disease duration revealed that serious infections were also less commonly observed in the pSS group (OR 0.62; 95% CI 0.44–0.86) than in SLE patients without sSS 47.…”
Section: Demographic Clinical and Serological Features Of Pss And Slementioning
confidence: 98%
“…A recent large multicenter study, which included 437 pSS patients and 2,926 SLE patients, evaluated the frequency of cardiovascular events, severe infections, and fibromyalgia (FM) in pSS patients in comparison to SLE patients without sSS 47. This comparative analysis was adjusted for demographical features, disease duration, and previous therapies with glucocorticoids, and antimalarial and immunosuppressive drugs 47.…”
Section: Demographic Clinical and Serological Features Of Pss And Slementioning
confidence: 99%
See 2 more Smart Citations